Influence of Accelerated Ageing on Indian Pines Seed - Bahar, Nawa (Indian Forester, 2018)
Effect of accelerated ageing on Indian pines seed namely Chir pine (Pinus roxburghii), Blue pine (P. waliichiana), Chilgoza pine (P. gerardiana) and Khasi pine (P. Khasiya) was investigated to evaluate their potential in term of germinability, seedling length, dry matter production and seedling vigour index. It Is evident from the results that the germination per cent of seed has little differences among the species and the highest seedling vigour index was estimated in chir pine (348.406). However, the lowest seedling vigour index was found in blue pine (271.296).